Village Downstream Politics and Accessibility of Islamic Microfinance in Junok Milkfish Production - Nurul Aulia; Mashudi; Dahruji (Penerbit Hellow Pustaka, 2025)
The milkfish pindang business in Junok Village, Sreseh District, Sampang Regency, is a leading business that is highly sought after by the local community. However, this business has not yet developed optimally and is still limited to the area. Therefore, efforts are needed to optimize village downstreaming and access to Islamic microfinance to support milkfish pindang production so that it can expand further and provide a greater economic impact for the community. This study aims to analyze the role of the village government in optimizing both of these aspects and contributing to sustainable local economic development. The research method used was qualitative, with data collection techniques through in-depth interviews and observation. The results show that the Junok village government has undertaken various efforts to optimize village downstreaming, including milkfish cultivation training, setting harvest schedules, and also plans to facilitate financing from Islamic microfinance institutions (LKMS). Despite several obstacles, such as a lack of financial knowledge among farmers and limited equipment, the village government continues to strive to address these issues through mentoring and education. Overall, the efforts made have been quite optimal and have the potential to support the development of the milkfish pindang business in the future.